2004
DOI: 10.1021/ma049576p
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Crystallization in Nanofilms of Poly(3-hydroxybutyrate)

Abstract: The aim of this work is to obtain amorphous thin films of poly(3-hydroxybutyrate) (PHB) at room temperature. The PHB thin films were obtained by spin-coating of chloroform−polymer solutions on glass substrate. The films were extensively characterized by X-ray diffraction and AFM. In this work it has been shown that the local interaction of the polar groups of the polymer with the glass substrate reduces the chain mobility, precluding the crystallization within a tens of nanometers thick region close to the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 32 publications
7
59
0
Order By: Relevance
“…This evidence has strong fundamental implications. For example, the reduction of tracer diffusivity and increase of crystallization time in proximity of an attractive interface, [4,5] are often explained in terms of increase of the glass transition temperature, [6] speculations which have not been experimentally verified. Moreover, the perturbations in D tr exert a non-negligible impact on the curing of polymer-based nanodevices: diffusion of small molecules in proximity of inorganic/ organic junctions is, in fact, a crucial mechanism underlying in many processing steps like, for example, solvent evaporation, crystallization, self-assembly, and phase segregation.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence has strong fundamental implications. For example, the reduction of tracer diffusivity and increase of crystallization time in proximity of an attractive interface, [4,5] are often explained in terms of increase of the glass transition temperature, [6] speculations which have not been experimentally verified. Moreover, the perturbations in D tr exert a non-negligible impact on the curing of polymer-based nanodevices: diffusion of small molecules in proximity of inorganic/ organic junctions is, in fact, a crucial mechanism underlying in many processing steps like, for example, solvent evaporation, crystallization, self-assembly, and phase segregation.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that within the first 90 Å from the surface the ordering of the polymer molecules is markedly enhanced. Such surface-related effects can also be found in other polymeric systems [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 71%
“…On the contrary, incorporation of P34HB promotes significant diffraction peaks especially at 2h of about 16.5°. This diffraction peak could be assigned to the (1 1 0)/(2 0 0) crystal plane of PLA or the (1 1 0) crystal plane of P34HB [24][25][26][27][28]. Therefore, it not easy to obtain information about crystallization of PLA in the blend fibers from the XRD profiles.…”
Section: Resultsmentioning
confidence: 99%